“I’d probably trip over it because it’s bumpy”: A qualitative exploration of the lived experiences of ambulatory children with cerebral palsy walking in challenging environments - Rebecca L. Walker; Thomas D. O’Brien; Gabor J. Barton; Bernie Carter; David M. Wright; Richard J. Foster (PLoS ONE, 2025)
Background Children with cerebral palsy experience regular falls, but their lived experiences of falls in the real-world are unknown. Understanding the perspectives of children and parents is important to gain deeper insight into how falls happen in real-world environments, especially since typical walking analyses are carried out over level-ground and may overlook everyday challenges to balance (e.g., uneven pavements when walking to school). Walk-along interviews can generate rich insights into children’s everyday life by discussing experiences while walking. Aim The Walk-Along Project aimed to explore lived experiences of ambulatory children with cerebral palsy to determine challenging walking environments that increase fall risk day-to-day, using walk-along interviews. Methods Twelve ambulatory children with cerebral palsy (12 ± 3 years old, 6 hemiplegia, 6 diplegia) and their parents took part in an outdoor walk-along interview. Previous fall experiences and everyday challenging environments that may increase fall risk were discussed. Action cameras and microphones captured walking environments and conversations, which were later synchronised, transcribed and analysed in NVivo using interpretive description. Results Two themes were generated (‘places where trips and falls occur’ and ‘things children do to control falls and manage consequences’) plus five subthemes (‘walking on bumpy and unstable ground’, ‘taking care, walking slower and avoiding places’, ‘distracting environments are dangerous environments’, ‘close calls and falls’, and ‘managing consequences and concerns’). The most common environment suggested to increase fall risk was uneven surfaces (e.g., grass potholes) with distractions (e.g., dogs barking). Conclusions The Walk-Along Project reveals novel insights about places that increase fall risk in ambulatory children with cerebral palsy, beyond what is currently known. The importance of considering both environmental challenges (e.g., uneven surfaces) and sensory challenges (e.g., distractions) is highlighted through children’s lived experiences. Future work should consider how interacting factors (e.g., distractions in uneven environments) increase fall-risk in ambulatory children with cerebral palsy, in order to understand mechanisms of falls for potential fall prevention programmes.